On the Way to Optoionics - Senocrate, Alessandro; Kotomin, Eugene; Maier, Joachim (Wiley Blackwell, 2020)
Based on the recent finding of significant ion conduction enhancement in iodide perovskites upon illumination, the potential of an emerging field ‘opto-ionics’ – that we define in parallelism to ‘opto-electronics’ – is explored. We emphasize that the major prerequisite is the identification of appropriate stable materials which can act as light-tunable electrolytes, permeation membranes, or electrodes. In this way, classic, but light-tunable electrochemical devices would be in reach. We also touch upon related issues such as sensing, switching, and catalysis, in which light effects on ionic charge carriers are also expected to be important.
Discussions with Michael Grätzel, Ursula Röthlisberger, Robert A. Evarestov and Bettina V. Lotsch are gratefully acknowledged.
Keywords: optoionics; ion conductivity; solid state ionics; lead halide perovskites; photoelectrochemical devices; materials science; Research Subject Categories::NATURAL SCIENCES::Physics